Estudo do tratamento térmico aplicado na produção do molho de tomate - Brumatti, Michael Rogério (Universidade Federal de São Carlos, 2019)
In the food indurtry, it is necessary for the final product to comply with certain requirements that the legislation requires for this product to be marketed. One such requirement is the amount of certain microoganisms that may be harmful to the product as well as to the consumer. Therefore, there is the heat treatment step in the process, where there are decimal reductions in the concentration of the target microorganisms making the final product commercially sterile. From this, it is proposed with this work to study the process used for heat treatment in a food industry through each stage of this process and also the calculation of the lethality of microorganisms, verifying its efficiency in relation to what the legislation requires. It can be concluded that the results are satisfactory, that is, the heat treatment process is efficient to reduce the target microorganisms, but it is possible to point improvements in some steps to gain practicality and confirm its efficiency. Finally, a tube shell heat exchanger was designed to verify the gains that this can bring to the process beyond its efficiency compared to that used in the company that is a double tube.
Study of heat treatment applied in the production of tomato sauce
Keywords: Tomate; Microorganismo; Tratamento térmico; Tomato; Microorganisms; Heat treatment; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA